Culture Wars, Local Government, and the Australia Day Controversy: Insights from Urban Politics Research. Issue 3 (3rd July 2019) - Chou, Mark; Busbridge, Rachel
ABSTRACT: In recent years, numerous Australian local councils have made headlines by deciding to cease or move the national Australia Day celebrations and citizenship ceremonies in recognition of the dispossession and trauma suffered by Aboriginal and Torres Strait Islander peoples. Focusing on the controversial decision of Yarra City Council in Victoria to cancel its 26 January Australia Day celebration and citizenship ceremony, this article examines key issues arising from urban culture war conflicts and the policy options available to Australian local councils when faced with contentious ideological issues.